2010
DOI: 10.1017/s0022112010000741
|View full text |Cite
|
Sign up to set email alerts
|

Effective slip in pressure-driven flow past super-hydrophobic stripes

Abstract: Super-hydrophobic array of grooves containing trapped gas (stripes), have the potential to greatly reduce drag and enhance mixing phenomena in microfluidic devices. Recent work has focused on idealized cases of stick-perfect slip stripes. Here, we analyze the experimentally more relevant situation of a pressure-driven flow past striped slip-stick surfaces with arbitrary local slip at the gas sectors. We derive approximate formulas for maximal (longitudinal) and minimal (transverse) directional effective slip l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
158
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(177 citation statements)
references
References 28 publications
18
158
0
1
Order By: Relevance
“…To start, the slip lengths on non-wetted surfaces were measured to be consistent with theoretical values for grates [25,26] and posts [6,27] ("Never-wetted" in Fig. 4).…”
Section: University Of California Los Angeles (Ucla) California 900mentioning
confidence: 60%
“…To start, the slip lengths on non-wetted surfaces were measured to be consistent with theoretical values for grates [25,26] and posts [6,27] ("Never-wetted" in Fig. 4).…”
Section: University Of California Los Angeles (Ucla) California 900mentioning
confidence: 60%
“…Analytical models and numerical simulations are useful tools in understanding slip lengths in laminar flows on a few simple surface patterns such as grates (ridges, trenches) (Philip 1972a, b;Lauga and Stone 2003;Belyaev and Vinogradova 2010a;Asmolov and Vinogradova 2012), posts (pillars) (Ybert et al 2007;Davis and Lauga 2010), and holes (Ybert et al 2007;Davis and Lauga 2009a), as shown in Fig. 2.…”
Section: Liquid Slips On Shpo Surfaces: Theoretical Predictionsmentioning
confidence: 99%
“…Let then φ 1 and φ 2 = δ/L be the area fractions of the solid and gas phases with φ 1 + φ 2 = 1. Pressure-driven flow past such stripes has been shown to depend on the direction of the flow, and the eigenvalues of the slip-length tensor [20] read [21] …”
Section: Electro-osmotic Velocity In Eigendirectionsmentioning
confidence: 99%